Transcript profiling and DNA damage in the European eel (Anguilla anguilla L.) exposed to 7,12-dimethylbenz[a]anthracene - Nogueira, Patrícia
The molecular responses induced during and after an acute exposure to 7,12-dimethylbenz[a]anthracene(DMBA)were analysed in liver, gill and blood cells of juvenile Anguilla anguilla with the aim of developing molecular biomarkers of environmental PAH pollution. Changes in the mRNA expression levels of the cell cycle checkpoint-related rad1 gene and the mRNAs of differentially expressed genes by suppression subtractive hybridization (SSH) were analysed in the liver, and related to well-established biomarkers: cyp1A1 mRNA expression and assessment of the DNA integrity using the comet assay and flowcytometry. DMBA exposure resulted in increased cyp1A1 mRNA levels, suggesting that cyp1A1 might be involved in the metabolism of DMBA. Global DNA damage, detected by the comet assay, was observed in the three tissues analysed but only blood cells showed chromosomal lesions as analysed by flow cytometry. Although DNA damage was found in the liver, no induction in rad1 gene was observed in this organ. The global SSH approach revealed that mRNAs of genes related to xenobiotic metabolism, immune processes and cytoskeleton dynamics were differentially expressed in DMBA-exposed eel livers, highlighting the complexity in the response observed in fish exposed to a genotoxic agent and providing directions for new biomarker development.